LEGAL PROTECTION OF DIPLOMATIC REPRESENTATIVE BUILDING ASSESSED FROM THE PERSPECTIVE OF THE 1961 WINA CONVENTION (Case Study: Suicide Bombing In Kabul Afghanistan Near United States Embassy) - Luh Ewik Lindasari; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Jurnal Pendidikan Kewarganegaraan Undiksha, 2020)
The study aims to identify and analysts the legal protections of diplomatic buildings of the United States are reviewed from the perspective of the Vienna Convention 1961 as well as the recipient state answer of Kabul Afghanistan in the case of suicide bombing near the U.S. embassy. The study uses a type of normative legal research through a conceptual approach, a statutory approach and a historical approach that is then analyzers by using primary, secondary, and tertiary legal substances. The results showed that the protection of the law against diplomatic buildings is governed in article 25 of the 1961 Vienna Convention describing the building of representatives and facilities therein can not be contested by the recipient State obliged to provide facilities to support the activities of representatives outside the country and the form of liability of the recipient of Afghanistan to the diplomatic buildings by replacing any damages for both physical damage and discomfort experienced by 1961 United , as well as deploying security officers to anticipate follow-up attacks by the Taliban against the environment of United States diplomatic buildings